An educational beit midrash as a bridge between religious and secular identity - Galia Semo; Doly Eliyahu-Levi (Humanities & Social Sciences Communications)
Abstract This qualitative-phenomenological study presents the contribution of the educational beit midrash, a setting that is centered on a multidimensional engagement with Jewish and modern Hebrew texts. This unique preoccupation with Jewish canon texts also expresses educational-pedagogical innovation because it is neither bound by the religious-orthodox study limitations nor subject to predetermined educational goals. The research tool was an in-depth interview, conducted with 17 Bible teachers. Content analysis revealed three innovative realms of the educational beit midrash – pedagogical space, instruction, and learners. The pedagogical realm is pluralistic and egalitarian, based on collaborative interdisciplinary learning and listening. Instruction is characterized by professional freedom, and the learners’ realm reveals a varied learners community that enjoys introspection, individual and subjective thinking, and forming a Jewish-Israeli identity and belonging to the immediate and broader community. These research findings are significant for both teacher training and professional development, and the beit midrash method may enable a deep, inquisitive, and formative experience of intellectual dialogue.